Advances in Neural Networks Computational Intelligence for ICT - Bassis, Simone; Esposito, Anna.; Morabito, Francesco Carlo; Pasero, Eros.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This carefully edited book is putting emphasis on computational and artificial intelligent methods for learning and their relative applications in robotics, embedded systems, and ICT interfaces for psychological and neurological diseases. The book is a follow-up of the scientific workshop on Neural Networks (WIRN 2015) held in Vietri sul Mare, Italy, from the 20th to the 22nd of May 2015. The workshop, at its 27th edition became a traditional scientific event that brought together scientists from many countries, and several scientific disciplines. Each chapter is an extended version of the original contribution presented at the workshop, and together with the reviewers' peer revisions it also benefits from the live discussion during the presentation. The content of book is organized in the following sections. 1. Introduction, 2. Machine Learning, 3. Artificial Neural Networks: Algorithms and models, 4. Intelligent Cyberphysical and Embedded System, 5. Computational Intelligence Methods for Biomedical ICT in Neurological Diseases, 6. Neural Networks-Based Approaches to Industrial Processes, 7. Reconfigurable ModularAdaptive Smart Robotic Systems for Optoelectronics Industry: The White'R Instantiation This book is unique in proposing a holistic and multidisciplinary approach to implement autonomous, and complex Human Computer Interfaces. .
I Introductory chapter -- II Machine Learning -- III Articial Neural Networks: Algorithms and Models -- IV Computational Intelligence Methods for Biomedical ICT in Neurological Diseases -- V Neural Networks-based Approaches to Industrial Processes -- VI Intelligent Cyber-physical and Embedded Systems -- VII Recongurable- Modular- Adaptive- smart Robotic Systems for Optoelectronics Industry: The White'R Instantiation.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence